Perbuatan Melawan Hukum dalam Kasus Pertanahan Studi Perbandingan antara Indonesia dan Prancis - Putu Davis Justin Thenata; Ryan Jovan Susanto; Jeanette Olivia Kurniawati; Jessica Carol Lee (Jurnal Syntax Admiration, 2024)
Unlawful Actions (PMH) in land cases is an important issue in the legal system in various countries, including Indonesia and France. Although both countries have similar basic principles regarding PMH, there are fundamental differences in the way they are regulated and implemented, especially in the land context. This research aims to analyze the comparison between the PMH concept in Indonesia and France, with a focus on resolving land disputes. The method used is a comparative approach, comparing the legal provisions applicable in both countries, as well as the dispute resolution mechanisms applied in practice. The research results show that although there are similarities in the aim of protecting land rights and providing compensation to injured parties, each country has different legal characteristics in dealing with unlawful acts in the land context. In Indonesia, dispute resolution is more formal and bureaucratic, while in France it prioritizes mediation and a social approach. Apart from that, the difference in the application of subjective and objective responsibility is also an important differentiating factor in law enforcement related to PMH.